2004
DOI: 10.1007/bf02975115
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Diabetic activities of fucosterol fromPelvetia siliquosa

Abstract: Fucosterol isolated from Pelvetia siliquosa was tested for its anti-diabetic activity in vivo. Fucosterol, when administered orally at 30 mg/kg in streptozotocin-induced diabetic rats, was caused a significant decrease in serum glucose concentrations, and exhibited an inhibition of sorbitol accumulations in the lenses. Fucosterol, when administered orally at 300 mg/kg in epinephrine-induced diabetic rats, was also caused an inhibition of blood glucose level and glycogen degradation. These results demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(76 citation statements)
references
References 6 publications
0
76
0
Order By: Relevance
“…Ethyl acetate extract of S. wightii showed the presence of fucosterol, which has already been reported to have antidiabetic properties (Lee et al 2004). Fucosterol is a natural compound, mainly present in marine algae, which is used in the treatment of diabetes by inhibiting glycogen breakdown in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethyl acetate extract of S. wightii showed the presence of fucosterol, which has already been reported to have antidiabetic properties (Lee et al 2004). Fucosterol is a natural compound, mainly present in marine algae, which is used in the treatment of diabetes by inhibiting glycogen breakdown in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…This may also significantly delay carbohydrate digestion and glucose absorption. The presence of fucosterol, and its antidiabetic, hepatoprotective and antioxidant activity, has been reported in the marine algae Pelvetia (Lee et al 2004). The identified compounds in the extracts of both algal species showed the presence of major saturated and unsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Results of our previous studies indicate that the ether fraction of P. siliquosa exhibits hepatoprotective and glucoselowering effects, and fucosterol isolated from P. siliquosa has antioxidant and antidiabetic activities (Lee et al, 2002(Lee et al, , 2003(Lee et al, , 2004b. Additionally, it has been reported that fucosterol decreases angiotensin-converting enzyme levels, with a reduction in the glucocorticoid receptor in endothelial cells and inhibits the lymphatic absorption of cholesterol in rats (Hagiwara et al, 1986;Ikeda et al, 1988).…”
Section: Introdutionmentioning
confidence: 97%
“…Phlorotannins have been clarified to exhibit anti-diabetic (Lee, Shin, Kim, & Lee, 2004), anti-oxidation (Ahn et al, 2007), anti-cancer (Kong, Kim, Yoon, & Kim, 2009;Yang, Zeng, Dong, Liu, & Li, 2010), and anti-HIV (Ahn et al, 2004) (Table 1) activities.…”
Section: Phlorotanninsmentioning
confidence: 99%